222 DECISIve – DiagnosE using the Central veIn SIgn. A study comparing T2* MRI and lumbar puncture. Issue 6 (27th May 2022) - Allen, Christopher Martin; Morgan, Paul; Craner, Matthew; Tallantyre, Emma; Schmierer, Klaus; Dineen, Robert; Fitzsimmons, Deborah; DasNair, Roshan; Partlett, Christopher; Evangelou, Nikos
Abstract : Can a brain T2* MRI scan replace lumbar puncture in the diagnostic pathway of MS? We will present the preliminary data from DECISIve, a National Institute for Health Research – Research for Patient Benefit funded multicentre study. Clinical Trials reference: NCT04024969 Due to the revised 2017 McDonald diagnostic criteria, many more people are undergoing lumbar punctures, resulting in discomfort and additional costs to the NHS. Brain lesions with a central vein, detected with T2* MRI are thought to be characteristic of MS. Using a single group superiority diagnostic accuracy study, our primary research question is: Is T2* MRI a more sensitive diagnostic test than lumbar puncture with oligoclonal band examination, amongst people at first clinical presentation with possible MS? Recruitment is now open across four neuroscience centres for a year and clinical follow up will last 18 months to establish the diagnosis. We will compare the accuracy, speed, costs and acceptability of the different tests needed to make a diagnosis of MS and establish if most lumbar punctures can be replaced by a slightly longer MRI scan. christopher.allen@nottingham.ac.uk